Teachers’ Perceptions of Open Educational Resources: The Case of Open Resources for English Language Teaching (ORELT) in Kenya - Orwenjo, Daniel Ochieng; Erastus, Fridah Kanana (Journal of Learning for Development, 2021)
The use of Open Educational Resources (OERs) in the teaching and learning of various subjects is a relatively new innovation in the Kenyan school system. With the advent and subsequent liberalization of ICT, material developers are subsequently shifting away from the traditional modes of material development in the form of textbooks and other “canonical” formats which require the teacher to use them as they are handed down without any input or modification. The Open Resources for English Language Teaching (ORELT) is one such educational innovation. This paper reports the findings of a baseline survey conducted in Kenya with a view to finding out the views and perceptions of Kenyan Junior Secondary School Teachers with regard to the adoption of open resources for the teaching of English language in Kenyan secondary schools. Sixty (60) JSS teachers of English from rural and urban schools and of mixed gender were invited for a four day ORELT in-service induction workshop at the Kenyatta University Conference Centre. The teachers were then given ORELT materials in form of CDs and textbooks for use in teaching English in their schools. They were also registered on the online ORELT platform and each given log in credentials to enable them access freely access the materials and freely interact with fellow teachers throughout the commonwealth. The study reports that whereas teachers are ready to embrace the use of open resources, they have varying perceptions on the suitability and potential efficacy of open resources in Kenyan classrooms. It also emerges that such differing perceptions are constrained by institutional, cultural, pedagogical and personal factors. Accordingly, the study recommends a more structured, inclusive bottoms up approach to any educational innovation as a means of ensuring success.